INVESTIGATION ON THE BIOSORPTION OF MANGANESE USING TEA LEAVES AND TEA FIBERS (camellia sinensis) AS ADSORBENTS - Etim, Emmanuel E.; Yakubu, Shedrach; Undie, David Akpanke; Shinggu, John Paul (Unesa Journal of Chemistry, 2024)
Heavy metal-containing liquid effluents pose a health and environmental risk due to the rapid industrialization of businesses like mining, petrochemicals, fertilizers, and pesticides. The adsorption of manganese from an aqueous solution utilizing biosorbents such as tea leaves and tea fibers is the subject of this study. The adsorption process was studied by varying the initial concentration, adsorption dosage, time, temperature, and pH of the adsorbents. The FTIR results confirmed the presence of -OH, -NH2, C=O providing binding sites in both tea leaves and fibers. The research uses Langmuir and Freundlich adsorption isotherms, with Freundlich the best fitting for tea fiber and Langmuir for tea leaves. Kinetic studies show second-order kinetics is better for both, confirming an endothermic biosorption process.